Simple synthesis of gold-decorated silica nanoparticles by in situ precipitation method with new plasmonic properties - Félix, Lizbet León (2021)
We describe a simple method for the preparation of gold-decorated silica (SiO₂) nanoparticles (NPs) by the in situ precipitation method using simple BH₄⁻ ions reduction as a procedure, where BH₄⁻ ions are adsorbed onto PEI-functionalized SiO₂ NPs for stabilizing and reducing gold ions onto PEI-SiO₂ surface in water under ambient conditions. The result was 3-nm gold nanoshell NPs attached to SiO₂ core (~ 75 nm) with a surface plasmon resonance (SPR) at ~ 680 nm. SPR band is associated with Au NP aggregates that arise from strong interparticle interaction. This is an alternative to the gold-seeding methods and the use of anionic gold species for the obtention of gold-decorated SiO₂ NPs with an important red-shift in UV–Vis absorption and with potential applications in biosensors and photothermal therapy.